Verification of data integrity and co-operative loss recovery for secure data storage in cloud computing. Issue 1 (1st January 2019) - Rejin, Paul R; Paul, Raj D
Abstract: In Cloud Computing, the data stored in the external servers may be tampered or deleted by unauthorized persons or selfish Cloud Service Providers (CSPs). Hence, the Cloud Data Owners (CDOs) have to provide assurance to the integrity and correctness of the stored data in the server. In this paper, a Verification of Data Integrity and Co-operative Loss Recovery technique for secure data storage in Cloud Computing is proposed. In this technique, a ciphertext file is split into various cipher blocks and distributed to randomly selected cloud service providers (CSPs) by the cloud data owner (CDO). If a cloud data user (CDU) wants to access any file, the corresponding ciphertext file is reconstructed from the blocks and downloaded by the user. The file can be decrypted if the attribute set of the user matches the access policy of the application. By simulation results, we show that the proposed technique enhances the data integrity and confidentiality. GraphicalAbstract: